The Kafori Fm (Ségou Group, Sénégal) and relics of West-African post-Birimian volcanism - (:unkn) unknown (My University, 2011)
Part of the new geological mapping of Eastern Senegal (PASMI project, EU funding) deals with the Ségou / Madina-Kouta Supergroup that locally begins by a polygenic, highly heterometric distinctive conglomeratic level. This particular facies, ascribed to the Kafori Formation (Stenian to Tonian), constitutes an unique geodynamic marker in West Africa, as it testifies for Late Paleoproterozoic (post-Birimian) volcanic events unrecorded in any outcrop at regional scale. The Kafori Fm presents strong thickness variations at regional scale, from some decimeters to more than 40 meters. In sections where the Formation is the thickest, spectacular cliff outcrops show several superimposed metric bodies with alternations of conglomeratic facies of clast-supported and matrix-supported types. Matrix is usually unsorted, composed of millimetric, subangulous and translucent quartz grains and an important proportion of angulous millimetric to centimetric, feldspar grains and pegmatite clasts. The matrix is interpreted as derived from weathering and erosion of local Birimian granitoids. Clasts are particularly interesting by their heterometry (from pebbles to boulders, up to 70cm) and their highly various lithology. Pebble to boulder typology underlines a great variety of clast origin: - Abundant rhyolithic boulders (with 2 distinct facies, one of fresh appearance, grey in colour, another of reddish colour strongly weathered); - Subangular pebbles and cobbles of pelites, micaschists, foliated quartzites and granitoids from the local Birimian basement; - Very frequent, subrounded, milky white quartz pebbles, sometimes preserved as tourmaline quartz vein fragments of multidecimetric size; - Scattered pebbles and cobbles of less common lithologies but known of Birimian origin at regional scale: tourmaline-rich pegmatite, gabbro, volcanic breccia, undifferentiated volcanic rocks, magmatic facies with graphical texture. Sedimentological features collected in the Kafori For
Keywords: African Research